2018
DOI: 10.1152/ajplung.00477.2017
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous pulmonary hypertension in genetic mouse models of natural killer cell deficiency

Abstract: Natural killer (NK) cells are cytotoxic innate lymphoid cells with an established role in the regulation of vascular structure in pregnancy and cancer. Impaired NK cell function has been identified in patients with pulmonary arterial hypertension (PAH), a disease of obstructive vascular remodeling in the lungs, as well as in multiple rodent models of disease. However, the precise contribution of NK cell impairment to the initiation and progression of PAH remains unknown. Here, we report the development of spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…Moreover, it has been reported that NOD-SCID mice exhibit poor functional recovery and revascularization following myocardial infarction compared with immune-competent mice, which can be rescued by adoptive transfer of IL-2 stimulated NK cells 13 . NK cells have also been implicated in the pathobiology of PAH 17 , 18 . Nfil3 − / − mice that lack NFIL3 transcription factor and Ncr1-GFP mice that lack the NK cell activating receptor exhibit NK cell deficiency and develop spontaneously develop PH 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that NOD-SCID mice exhibit poor functional recovery and revascularization following myocardial infarction compared with immune-competent mice, which can be rescued by adoptive transfer of IL-2 stimulated NK cells 13 . NK cells have also been implicated in the pathobiology of PAH 17 , 18 . Nfil3 − / − mice that lack NFIL3 transcription factor and Ncr1-GFP mice that lack the NK cell activating receptor exhibit NK cell deficiency and develop spontaneously develop PH 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in two independent genetic mouse models for NK cell dysfunction, involving deficiency of the NFIL3 transcription factor or the NK activating receptor NKp46, enhanced RV systolic pressures and RV hypertrophy were found. In both models, this experimental PH development was linked to increased interleukin-23 (IL-23) production, possibly due to NK cells or impairment, leading to the increased production of IL-23 by pulmonary macrophages and other myeloid cell types [66]. Interestingly, IL-23 is known for its production of inflammatory cytokines, such as IL-17A/F, IL-21 and IL-22, and for driving naïve T cells to a TH17 phenotype [67].…”
Section: Natural Killer Cellsmentioning
confidence: 99%
“…These findings linked the ACE2/Ang-(1-7)/Mas axis with inflammation, activation of the angiotensin type 2 receptor, attenuated BLM-induced lung fibrosis, vascular remodelling, and increased RVSP, concomitant with a reduction of infiltrated macrophages (Rathinasabapathy, Horowitz, et al, 2018). These mechanisms are summarized in Figure 1.…”
Section: Renin-angiotensin Systemmentioning
confidence: 80%